Forage Mineral Concentrations in Grazed, Warm-Season Bahiagrass Pastures in Florida - Bob Myers; Lee McDowell; Cheryl Mackowiak; Ann Blount (EDIS)
AN243, a 4-page fact sheet by Bob Myer, Lee McDowell, Cheryl Mackowiak, and Ann Blount, discusses the concentrations of forage minerals in bahiagrass pastures for beef cattle, to determine adequate mineral levels and use of mineral supplements. Includes references. Published by the UF Department of Animal Science, July 2010.